Ekstrak Bawang Putih (Allium sativum) dan Ekspresi Insulin serta Derajat Insulitis Pankreas Tikus Sprague-Dawley yang Diinduksi Streptozotocin - Meira Dewi; Indra Wijaya; Noor Wijayahadi (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTAllium sativum, insulin expression and insulitis degree of pancreas Sprague-Dawley rat induced by streptozotocinBackground: The organic-sulphur content in Allium sativum has been scientifically proven to be a potent insulin-mimetic, antioxidant, and anti-inflammation agent by inhibiting the activity of NF-κβ. This research is aimed at finding out the effect of Allium sativum extract towards insulitis level and insulin expression in pancreas of Sprague-Dawley male rats.Method: This research used a randomized post test only controlled group design. There were 28 rats, two were randomly selected for the initial blood glucose test prior to treatment, two were selected on the tenth day after streptozotocin induction to ensure that all rats were in hyperglycaemia condition, and the remains as many as 24 rats were grouped into four groups: three treatmentgroups were administered with Allium sativum in levelled doses of 0.1, 0.25, 0.5 grams/kgBW/day for 14 days, and one group were act as control negative. Kruskall Wallis test continued with Mann Whitney test were used, with significance level of p<0.05.Results: The insulitis level and insulin expression of rats’ pancreas in the three treatment groups showed significant difference compared with the group without treatment showing dose-dependent result. However, it was not able to completely restore the damage pancreas.Conclusion: Allium sativum extract may play important role in restoring damage pancreas.Keywords: Allium sativum, streptozotocin, insulin expression, level of insulitisABSTRAKLatar belakang: Kandungan organosulfur pada Allium sativum secara ilmiah memiliki berbagai potensi sebagai agen insulinomimetic, antioksidan dan antiinflamasi dengan menghambat aktivitas NF-κß. Penelitian ini bertujuan untuk melihat pengaruh pemberian ekstrak Allium sativum terhadap derajat insulitis dan ekspresi insulin pankreas tikus Sprague-Dawley jantan.Metode: Penelitian ini menggunakan desain randomized post test only controlled group. Hewan coba sebanyak 28 ekor tikus, dua ekor tikus diambil acak sebelum perlakuan untuk diperiksa gula darah awal, dua ekor setelah hari ke sepuluh induksi streptozotocin untuk memastikan tikus sudah dalam keadaan hiperglikemia dan sisanya dua puluh empat ekor tikus, dibagi dalam empat kelompok: tiga kelompok perlakuan diberi ekstrak Allium sativum dosis bertingkat 0,1, 0,25, 0,50 g/kgBB/hari selama 14 hari, dan satu kelompok sebagai kontrol negatif. Digunakan uji non parametrik Kruskal Wallis dilanjutkan Mann Whitney dengan taraf kemaknaan p<0,05.Hasil: Derajat insulitis dan ekspresi insulin pankreas tikus pada ketiga kelompok perlakuan menunjukkan perbedaan bermakna dibandingkan dengan kelompok yang tidak mendapat perlakuan dan bersifat dose – dependent, namun belum dapat mengembalikan pulau Langerhan kembali ke keadaan normal.Simpulan: Ekstrak Allium sativum berpeluang memperbaiki pankreas yang rusak.